Observations on the exploitation of penaeid prawn resources in the Palk Bay off Mandapam during 1986 - ’93 - Maheswarudu, G; Manickam, P E Sampson; Rao, P Vedavyasa; Arputharaj, M R (Indian Journal of Fisheries, 2011)
The penaeid prawns contributed to 16.70% of the total trawl landings at Mandapam during 1986-’93. Out of the ten species represented in the catch, four species namely Penaeus semisulcatus, Metapenaeopsis stridulans, Trachypenaeus pescadoreensis and Metapenaeus burkenroadi supported the fishery throughout the year. Contributing to over 50%, P. semisulcatus was the dominant species, followed by M. stridulans. Over the years a gradual decline of P.semisulcatus in the species percentage composition and a steady increase of that of M. stridulans was observed. The change in the species composition during 1986-’93 has been discussed. May to August was the peak season for the fishery. Two peak seasons, one during May-August and the other during November-December were observed for P. semisulcatus. The annual fishing effort fluctuated between 3,54,055 and 6,48,513 hours with an average of 4,90,361 hours. The annual prawn catch ranged from 561 to 1,065.8 t, the average annual catch being 703.5 t. The annual catch per hour ranged from 0.8 to 2 kg. The MSY and corresponding optimum fishing effort was 726.2 t and 5,61,415 hours respectively.